Implementasi Kepemimpinan Instruksional Kepala sekolah DI SMP Negeri 2 Warungasem - Kundiastuti, Kundiastuti; Darojah, Darojah; Tumiyati, Tumiyati; Nurkolis, Nurkolis (Cetta: Jurnal Ilmu Pendidikan, 2025)
Instructional leadership is a key factor that influences the quality of the teaching and learning process. This study examines the implementation of instructional leadership in SMP Negeri 2 Warungasem. The purpose of this study is to find out how the implementation of learning leadership is carried out, the challenges faced by the principal, and the impact on the quality of learning in the application of instructional leadership. The research method used is descriptive qualitative approach, with data collection through interview, observation, and document study. The results showed that instructional leadership plays an important role in the formulation and implementation of the school's vision and mission, as well as the management of curriculum and learning programs. However, there are some challenges in its implementation, including limited resources and lack of collaboration with external stakeholders. This research is expected to provide insights into the importance of effective leadership in improving the quality of education in schools and to provide guidance for the development of more effective and innovative learner-centered education policies.